Some Characterizations of Bloch Functions (Analysis in Theory and Applications, 2018)
We define Bloch-type functions of $\mathcal{C}^1(\mathbb{D})$ on the unit disk of complex plane $\mathbb{C}$ and characterize them in terms of weighted Lipschitz functions. We also discussthe boundedness of a composition operator $C_{φ}$\u00a0acting between two Bloch-type spaces.These obtained results generalize the corresponding known ones to the setting of $\mathcal{C}^1(\mathbb{D})$.
Keywords: Bloch space; majorant; composition operator.